Faktor Penentu Keputusan Masyarakat Menjadi Pekerja Migran Indonesia (Studi Kasus : di Desa Bongas Kecamatan Bongas Kabupaten Indramayu) - Zulfan Fikriansyah; Aan Julia (Bandung Conference Series: Economics Studies, 2023)
Abstract. Population growth, unemployment and poverty are economic problems that affect humans directly. The Indonesian government's program of efforts to deal with problems of population growth, unemployment and poverty is to take advantage of international job opportunities and facilitate workers who want to migrate abroad to find work. Indramayu Regency is the largest district in West Java as a distributor of migrant workers. One of the villages contributing to migrant workers in Indramayu Regency is Bongas Village, Bongas Sub-district, where Bongas Village holds the title as a village that sells people and a village that supplies Indonesian migrant workers (PMI). There are many programs formulated by the Bongas Village Government and the Kusuma Bongas Foundation such as opening open schools, business training, providing Life Skills, etc. As an effort to empower PMI and post-PMI, in fact, it can't stop the interest of migrant workers from Bongas Village to keep migrating. The purpose of this study was to identify the driving and pulling factors for the residents of Bongas Village, Bongas Subdistrict, in becoming PMI. This research uses descriptive quantitative method. The data used are primary field survey data with 100 respondents consisting of 73 post-PMI respondents and 27 family respondents. Secondary data from BNP2TKI Indramayu, DISNAKER Indramayu, Village Profile. The analysis in this study uses a Likert scale. Based on the results of the study that the driving factor for determining the decision of the people of Bongas Village in becoming migrant workers is the skill and expertise indicator with an average score of 383 and the highest pull factor is the wage indicator with an average score of 398. Then Of the two variables, namely push and pull variables, the highest average as a determinant of migration is the pull variable on the wage indicator. Abstrak. Pertumbuhan penduduk, pengangguran dan kemiskinan merupakan masalah ekonomi yang mempengaruhi manusia secara langsung. Program upaya pemerintah Indonesia dalam menangani masalah pertumbuhan penduduk, pengangguran dan kemiskinan yaitu dengan memanfaatkan kesempatan kerja Internasional dan memfasilitasi tenaga kerja yang ingin bermigrasi ke luar negeri untuk mencari pekerjaan. Kabupaten Indramayu merupakan kabupaten terbesar di Jawa Barat sebagai penyalur pekerja migran. Salah satu Desa penyumbang pekerja migran di Kabupaten Indramayu adalah Desa Bongas Kecamatan Bongas dimana Desa Bongas menyandang predikat sebagai Desa penjual manusia dan Desa pemasok pekerja migran Indonesia (PMI). Ada banyak program yang di rumuskan oleh Pemerintah Desa Bongas dan Yayasan Kusuma Bongas seperti membuka sekolah terbuka, pelatihan usaha, memberikan pembekalan Life Skill dll. Sebagai upaya pemberdayaan PMI dan purna PMI nyatanya tidak bisa menyuturkan minat pekerja migran asal Desa Bongas untuk tetap bermigrasi. Tujuan penelitian ini adalah untuk mengidentifikasi faktor pendorong dan faktor penarik minat penduduk Desa Bongas Kecamatan Bongas dalam menjadi PMI. Penelitian ini menggunakan metode deskriptif kuantitatif. Data yang digunakan yaitu data primer survei lapangan dengan responden 100 orang terdiri dari 73 responden Purna PMI dan 27 responden keluarga. Data sekunder dari BNP2TKI Indramayu, DISNAKER Indramayu, Profil Desa. Analisis dalam penelitian ini menggunakan skala likert. Berdasarkan hasil penelitian bahwa faktor pendorong penentu keputusan masyarakat Desa Bongas dalam menjadi pekerja migran yang paling tinggi adalah indikator keterampilan dan keahlian dengan nilai rata-rata skor sebesar 383 dan faktor penarik yang paling tinggi adalah indikator upah dengan nilai rata-rata skor sebesar 398. Kemudian dari kedua variabel yaitu variabel pendorong dan penarik di rataratakan yang paling tinggi sebagai penentu migrasi.